THE IMPACT OF TEXTILE DYES ON THE BIOCHEMISTRY AND HISTOLOGY OF LIVER, A FRESHWATER FISH, TILAPIA, OREOCHROMIS MOSSAMBICUS (PETERS.) - L.SRIPRIYA,; VIJAYALAKSHMI M,; SUMATHY R,; SHARMILA J, (International Journal of Pharma and Bio Sciences, 2014)
The investigations were conducted on fresh water fish Oreochromis mossambicus (Peters.) to check out the effect of different concentrations of textile dyes on antioxidant status as Glutathione reductase, Catalase and Reduced glutathione,marker enzymes such as Aspartate transaminase (AST), Alanine transaminase (ALT) and Lactate dehydrogenase (LDH),electrolytes such as Calcium, Magnesium and Sodium, essential nutrients such as Vitamin C, Folic acid and Lysine, Protein pattern, conformation of biomolecules and histology of liver for different duration of days. The different concentrations of textile dyes were 0.5, 1.0 and 1.5 ppm and exposure period were 7, 14 and 21 days. The results indicate that chronic exposure of fish to 1.5 ppm of textile dyes for 21 days significantly altered the antioxidant status and activities of enzymes. It was observed that there is a decrease in concentration of calcium, magnesium and sodium in 7, 14, 21 days group when compared to control group which shows an adverse effect of textile days on ionic and osmotic regulation. A significant depletion of essential nutrients such as vitamin C, Folic acid and Lysine was observed in the present study, which disturbed the growth and metabolism of fish. Electrophoretic protein pattern was also demonstrated which proved negative impacts of the textile dyes on the tissue, liver of the present studied fish. Structural variations in the biomolecules especially protein was demonstrated by FT-IR. The main histological changes observed in liver are hyperemia, necrosis and degeneration.